Promising Antioxidative Effect of Berberine in Cardiovascular Diseases - An, Na; Zhang, Guoxia; Li, Yingjian; Yuan, Chao; Yang, Fan; Zhang, Lijing; Gao, Yonghong; Xing, Yanwei (Frontiers in Pharmacology, 2022)
Berberine (BBR), an important quaternary benzylisoquinoline alkaloid, has been used in Chinese traditional medicine for over 3000 years. BBR has been shown in both traditional and modern medicine to have a wide range of pharmacological actions, including hypoglycemic, hypolipidemic, anti-obesity, hepatoprotective, anti-inflammatory, and antioxidant activities. The unregulated reaction chain induced by oxidative stress as a crucial mechanism result in myocardial damage, which is involved in the pathogenesis and progression of many cardiovascular diseases (CVDs). Numerous researches have established that BBR protect myocardium and may be beneficial in the treatment of CVDs. Given that the pivotal role of oxidative stress in CVDs, the pharmacological effects of BBR in the treatment and/or management of CVDs have strongly attracted the attention of scholars. Therefore, this review sums up the prevention and treatment mechanisms of BBR in CVDs from in vitro, in vivo, and finally to the clinical field trials timely. We summarized the antioxidant stress of BBR in the management of coronary atherosclerosis and myocardial ischemia/reperfusion; it also analyzes the pathogenesis of oxidative stress in arrhythmia and heart failure and the therapeutic effects of BBR. In short, BBR is a hopeful drug candidate for the treatment of CVDs, which can intervene in the process of CVDs from multiple angles and different aspects. Therefore, if we want to apply it to the clinic on a large scale, more comprehensive, intensive, and detailed researches are needed to be carried out to clarify the molecular mechanism and targets of BBR.